Lithuanian Insurance Services Market Competitiveness and Impact of Globalization and Integration - Kindurys, Vytautas (Ekonomika, 2001)
Lithuanian insurance services market is in transitional period, inadequately developed. Its structure is oligopoly. Competition in Lithuanian insurance services market is not tough. Globalization and integration processes in global insurance market have influence on Lithuanian insurance services market competitiveness.Recently urge of western in.urance companies (groups) towards Lithuanian insurance services market became more active. This has increased the competition level in this market. At present the tendency of insurance companies merges becomes apparent. This is peculiar consequence of tougher competition.Insurance companies merge with banks attempting to stand in market. Thus, they are strengthening their position in market.Insurance brokers play the more important role in Lithuanian insurance services market. Competition in insurance services market is sharpened by their active activities as well.